Analisis Strategi Breakout dalam Pengambilan Keputusan Order Pada Trading Forex - Vincentius Bintang Febrianto; Agustinus Noertjahyana (Jurnal Infra, 2021)
Trading on forex with a strategy is an effort made by traders so that trading can be more profitable, one of which is using a breakout strategy and cannot be separated from determining the range of this strategy. However, in trading using a breakout strategy, sometimes some traders are not precise in determining the range. This can cause traders to lose profits. Therefore, it is necessary to establish an expert advisor program that is able to help traders make decisions in determining ranges. The expert advisor program mechanism that is created is to determine the initial reference range first to become the range amount that will be used for trading using the breakout strategy. The initial reference range is then copied to the highest and lowest prices in history. The program is then tested through backtesting.The results of tests carried out on the EUR / USD, GBP / USD, and USD / JPY pairs for 3 years can generate profits from obtained 4 initial reference ranges in various conditions of price movements. Of the three ranges of each pair on the H1 time frame, the most profitable range is the 107 pip range in the EUR / USD pair with a profit of 2528.64, the 100 pip range in the GBP / USD pair with a profit of 2628.31, the 74 pip range in the USD / JPY pair with a profit of 1691.47. In the H4 time frame, the most profitable range is 90 pips in the EUR / USD pair with a profit of 2093.06, 99 pips in the GBP / USD pair with a profit of 2429.07, 100 pips in the USD / JPY pair with a profit of 1279.94.